2012
DOI: 10.1089/scd.2012.0017
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Increases the Frequency of Circulating Hematopoietic Progenitor Cells, But Reduces Hematopoietic Colony-Forming Capacity

Abstract: Circulating hematopoietic progenitor cells (CPCs) may be triggered by physical exercise and/or normobaric hypoxia from the bone marrow. The aim of the study was to investigate the influence of physical exercise and normobaric hypoxia on CPC number and functionality in the peripheral blood as well as the involvement of oxidative stress parameters as possibly active agents. Ten healthy male subjects (25.3±4.4 years) underwent a standardized cycle incremental exercise test protocol (40 W+20 W/min) under either no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…In light of the well-documented association of obesity with breast cancer, we compared in the current study the abundance of circulating ASCs in obese and non-obese breast cancer survivors. Although there is published work on the effect of exercise on circulating endothelial cells (72) and hematopoietic progenitor cells (73), similar studies on circulating ASCs have not been reported. Therefore, we sought to assess the impact of exercise on circulating ASCs among the obese breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the well-documented association of obesity with breast cancer, we compared in the current study the abundance of circulating ASCs in obese and non-obese breast cancer survivors. Although there is published work on the effect of exercise on circulating endothelial cells (72) and hematopoietic progenitor cells (73), similar studies on circulating ASCs have not been reported. Therefore, we sought to assess the impact of exercise on circulating ASCs among the obese breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that IHH and ME may be more aggressive stimuli in older than for younger subjects. Some studies have reported a time-dependent increase in CPC count after a cycle incremental exercise test under normoxic or hypoxic conditions, increasing 10 min after exercise [21], during 240 min of strenuous exercise [22] and after a marathon race or 1500m field test [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have investigated the influence of physical exercise on total CPC numbers by flow cytometry [1], [2], [8] and colony-forming unit (CFU) assays [2], the proliferative capacity/functionality of CPCs in humans has only been addressed in our study [6]. The important question of which strenuous exercise-induced mechanisms affect CPC functionality, however, remains open and needs further elucidation.…”
Section: Introductionmentioning
confidence: 97%
“…Exercise has a complex influence on the body, making the exact mechanisms responsible for CPC mobilization and the influence on CPC functionality/proliferative capacity difficult to identify [5]. Previous studies have associated exercise-induced oxidative stress [6], cortisol (Co) [7], interleukin 6 (IL-6), growth hormones such as vascular endothelial growth factor (VEGF) [8], and granulocyte-colony stimulating factor (G-CSF) [9] with post-exercise increased peripheral CPC numbers. A possible influence of exercise-related peripheral blood (pb) free/bound norepinephrine (NE), free/bound epinephrine (EPI) and lactate (La) remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation